Staphylococcus aureus ‘Down Under’: contemporary epidemiology of S. aureus in Australia, New Zealand, and the South West Pacific - Williamson, D.; Coombs, Geoffrey; Nimmo, G. (Blackwell Publishing, 2014)
The clinical and molecular epidemiology of Staphylococcus aureus disease has changed considerably over the past two decades, particularly with the emergence and spread of community-associated methicillin-resistant S. aureus (CA-MRSA) clones. Indeed, some of the first global descriptions of CA-MRSA were from remote indigenous communities in Western Australia, and from Pacific Peoples in New Zealand. The epidemiology of S. aureus infections in the South West Pacific has several unique features, largely because of the relative geographical isolation and unique indigenous communities residing in this region. In particular, a number of distinct CA-MRSA clones circulate in Australia and New Zealand, such as sequence type (ST) 93 methicillin-resistant S. aureus (MRSA) (Queensland clone) and clonal complex 75 S. aureus (Staphylococcus argenteus) in Australia, and ST30 MRSA (Southwest Pacific clone) in New Zealand. In addition, there is a disproportionate burden of S. aureus disease in indigenous paediatric populations, particularly in remote Aboriginal communities in Australia, and in Pacific Peoples and Maori in New Zealand. In this review, we provide a contemporary overview of the clinical and molecular epidemiology of S. aureus disease in the South West Pacific region, with a particular focus on features distinct to this region.